Ideology and Christianity in Japan - Mervart, David (Social science Japan journal, 2010)
After volumes on the political philosophy of the Kyoto school (Goto-Jones 2005) and on the role of the left in Japanese democracy (Kersten and Williams 2006), Kiri Paramore's book is another recent addition to the series of monographs on Japanese history, thought and politics, the fruit of the cooperation between the Modern East Asia Research Centre at Leiden University and Routledge publishers. To get the main complaint out of the way first: the Routledge venue unfortunately accounts for most of the present title's shortcomings, namely the lethal combination of an exorbitant price and poor (if any) editing. One is puzzled by this suicidal strategy, for in the world of online dissemination of scholarly texts, it would seem that uncompromisingly high standards of review and editing remain almost the sole rationale for the continuing existence of the traditional publishing house.
Gesehen am 20.04.2023